Approximate Solutions of Combinatorial Problems via Quantum Relaxations - Bryce Fuller; Charles Hadfield; Jennifer R. Glick; Takashi Imamichi; Toshinari Itoko; J. Richard Thompson; Yang Jiao; M. Marna Kagele; W. Blom-Schieber Adriana; Rudy Raymond; Antonio Mezzacapo (IEEE Transactions on Quantum Engineering)
Combinatorial problems are formulated to find optimal designs within a fixed set of constraints and are commonly found across diverse engineering and scientific domains. Understanding how to best use quantum computers for combinatorial optimization remains an ongoing area of study. Here, we propose new methods for producing approximate solutions to quadratic unconstrained binary optimization problems, which are based on relaxations to local quantum Hamiltonians. We look specifically at approximating solutions for the maximum cut problem and its weighted version. These relaxations are defined through commutative maps, which in turn are constructed borrowing ideas from quantum random access codes. We establish relations between the spectra of the relaxed Hamiltonians and optimal cuts of the original problems, via two quantum rounding protocols. The first one is based on projections to random magic states. It produces average cuts that approximate the optimal one by a factor of least 0.555 or 0.625, depending on the relaxation chosen, if given access to a quantum state with energy between the optimal classical cut and the maximal relaxed energy. The second rounding protocol is deterministic and is based on the estimation of Pauli observables. The proposed quantum relaxations inherit memory compression from quantum random access codes, which allowed us to test the performances of the methods presented for 3-regular random graphs and a design problem motivated by industry for sizes up to 40 nodes, on superconducting quantum processors.